2005
DOI: 10.1068/p5416
|View full text |Cite
|
Sign up to set email alerts
|

Visually Perceived Eye Level and Horizontal Midline of the Body Trunk Influenced by Optic Flow

Abstract: The eye level and the horizontal midline of the body trunk can serve, respectively, as references for judging the vertical and horizontal egocentric directions. We investigated whether the optic-flow pattern, which is the dynamic motion information generated when one moves in the visual world, can be used by the visual system to determine and calibrate these two references. Using a virtual-reality setup to generate the optic-flow pattern, we showed that judged elevation of the eye level and the azimuth of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 69 publications
(80 reference statements)
4
34
0
1
Order By: Relevance
“…These data were obtained in a previous study with a different group of observers in our laboratory (B. Wu, 2004). Clearly, these data reveal that distance is underestimated in the dark when the ground surface is not visible Philbeck & Loomis, 1997;J. Wu et al, 2005).…”
Section: Resultsmentioning
confidence: 51%
See 4 more Smart Citations
“…These data were obtained in a previous study with a different group of observers in our laboratory (B. Wu, 2004). Clearly, these data reveal that distance is underestimated in the dark when the ground surface is not visible Philbeck & Loomis, 1997;J. Wu et al, 2005).…”
Section: Resultsmentioning
confidence: 51%
“…We believe this main effect of target distance is likely to be due to the observer's fixation position, because in a separate study at our laboratory (J. Wu et al, 2005) we found that the eye fixation position can affect the judged eye level. Recall that during the judged eye-level measurement in the present experiment, observers fixated their eyes on a reference target on the floor (immediately below the test target).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations